Country of Origin, Brand Image, and Attitude Toward the Brand on Wuling EV Purchase Intention - Roni Irawan; Maria Apsari Sugiat; Dedi Iskamto (Husnayain Business Review, 2026)
Purpose – This study aims to examine the influence of country of origin on purchase intention of Wuling electric vehicles in Indonesia, with brand image and attitude toward the brand as mediating variables. Methodology/Approach – A quantitative survey design was employed using a structured questionnaire to collect data from respondents who own Wuling electric vehicles. The purposive sampling technique was applied with an inclusion criterion of age between 21 and 55 years. A total of 419 respondents were successfully collected and included in the analysis. The analysis used SEM-PLS to evaluate the direct and indirect relationships between variables. Findings – The results revealed that country of origin does not exert a direct impact on the intention to purchase but significantly influences attitude toward the brand and brand image. Both mediators, attitude toward the brand and brand image, exert a significant impact on the intention to purchase and serve as effective pathways in strengthening the indirect influence of country of origin. Novelty/Value – This study highlights the strategic importance of brand image and consumer attitudes in shaping purchase intentions, particularly for Chinese automotive brands entering competitive markets. It also provides practical insights for Wuling and theoretical guidance for future research on international brands and consumer behavior in emerging markets.